2000
DOI: 10.1103/physrevb.62.6027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unitary impurities on non-STM types of tunneling in high-Tcsuperconductors

Abstract: Based on an extended Hubbard model, we present calculations of both the local (i.e., singlesite) and spatially-averaged differential tunneling conductance in d-wave superconductors containing nonmagnetic impurities in the unitary limit. Our results show that a random distribution of unitary impurities of any concentration can at most give rise to a finite zero-bias conductance (with no peak there) in spatially-averaged non-STM type of tunneling. This is in spite of the fact that local tunneling in the immediat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
57
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 60 publications
6
57
0
3
Order By: Relevance
“…The attribution of the maximum at the center of the STM pattern to an effect of hybridization of impurity wavefunctions with the states between the CuO 2 and the surface bears some similarity to an explanation which has been discussed previously in the framework of phenomenological tight binding models 14,15 . In this approach, the presence of the BiO and SrO layers serve to act as a "fork" or "filter" which forces the electron to tunnel with equal probability from the Bi site above the impurity to the Cu sites neighboring the impurity; thus the measured LDOS at the surface is found to reflect a linear combination of the impurity-induced wavefunctions on the nearest-neighbor Cu sites in the CuO 2 layer below.…”
Section: ( )mentioning
confidence: 91%
“…The attribution of the maximum at the center of the STM pattern to an effect of hybridization of impurity wavefunctions with the states between the CuO 2 and the surface bears some similarity to an explanation which has been discussed previously in the framework of phenomenological tight binding models 14,15 . In this approach, the presence of the BiO and SrO layers serve to act as a "fork" or "filter" which forces the electron to tunnel with equal probability from the Bi site above the impurity to the Cu sites neighboring the impurity; thus the measured LDOS at the surface is found to reflect a linear combination of the impurity-induced wavefunctions on the nearest-neighbor Cu sites in the CuO 2 layer below.…”
Section: ( )mentioning
confidence: 91%
“…The on-site potential scattering was taken to be either zero (Zhang et al, 2001) or very weak (Polkovnikov, 2002;Polkovnikov et al, 2001) so that the resonance peak is located very close to the Fermi energy. Zhu and Ting (Zhu and Ting, 2001b) took into account the quasiparticle scattering from a geometrical hole, where electrons are allowed to hop onto the four neighbors of the impurity site, and obtained a double-peak structure around the Fermi energy. They further (Zhu and Ting, 2001c) considered the potential scattering term to be in the unitary limit (U → ∞), and found that the Kondo resonance effect is weaved into that from the strong potential scattering to determine the low energy quasiparticle states.…”
mentioning
confidence: 99%
“…The discrepancies between experiments and the potential scattering scenario have led to the suggestion of various filter functions motivated by the fact that the measurements are performed on the topmost BiO layer whereas the nonmagnetic impurity substitutes a Cu atom in the CuO 2 plane two layers below the top BiO layer [8,9,10]. The significance of the filter functions remains controversial.…”
mentioning
confidence: 99%